Characteristics Of Cogon Grass Fibre Reinforced Thermoplastic Cassava Starch Biocomposite: Water Absorption And Physical Properties - Jumaidin, Ridhwan; Ab Rahman, Mohd Hidayat; Ahmad, Mohd Nazri; Wahi, Mohammad Khalid; Yaakob, Mohd Yuhazri; Maidin, Nurul Ain; Osman, Mohd Hairizal; Sutan Saidi, Zulhelmi Asyul; Ahmad Ilyas, Rushdan (Penerbit Akademia Baru, 2019)
The aim of this study is to investigate the characteristic of thermoplastic cassava starch (TPCS) composites containing cogon grass fiber (CGF) in the range of 1, 3, and 5 wt. %. Initially, the mixture of TPCS and CGF are prepared by pre-mixing using a high-speed mixer at 3000 rpm for 12 min. Then, the thermoplastic composites were pressed at 160°C for 35 min by using a compression molding machine. The composites were characterized for its moisture content, water absorption, thickness swelling and water solubility characteristics. Inclusion of 5 wt. % loading had significantly reduced the thickness swelling and water solubility of the biocomposites by 5.38% and 7.82%, respectively, compared with the neat TPCS. The moisture content and water absorption of the composites did not show significant changes following the addition of CGF. Overall, the incorporation of CGF into TPCS has enhanced the functional properties of the composites for short-life product applications.